Função sistólica do ventrículo esquerdo pela ecocardiografia convencional e speckle tracking bidimensional em gatos clinicamente saudáveis e com cardiomiopatia fenótipo hipertrófica - Coelho, Mariana de Resende (2022)
Two-dimensional speckle tracking echocardiography (2D-STE) has been evaluated for its potential to provide an early diagnosis of left ventricular systolic dysfunction, since it makes possible to obtain myocardial deformation through strain (St) and strain rate (SR) indices. The objectives of this study were to compare the two-dimensional echocardiography variables, longitudinal strain (St) and strain rate (SR) between asymptomatic cats with hypertrophic phenotype cardiomyopathy (HCM) and clinically healthy cats; to compare these variables in clinically healthy cats of different age groups, determine reference intervals (RIs) and, also, evaluate the agreement between the left apical 4-chamber (AP4C) and right longitudinal 4- chamber (LD4C) views for longitudinal St/SR and volume variables (ejection fraction – EF and systolic volume). To determine the RIs of the two-dimensional echocardiographic and longitudinal St/SR variables, 106 cats were selected and divided into groups according to age: G1 (37 animals) = kittens (< 1 year); G2 (53 animals) = young adult (1 to 6 years old), G3 (16 animals) = adult (7 to 10 years old). The group of animals with HCM (13 animals) was compared with healthy cats (106 animals) for the variables of conventional echocardiography and longitudinal St/SR. There was agreement between the AP4C and LD4C views to obtain the ejection fraction (EF) measured by the uniplanar modified Simpson method in healthy cats. There was no statistically significant difference between healthy and heart diseased cats for the longitudinal St and SR variables and for longitudinal St in healthy cats of different age groups. There was a difference only for the endocardial SR variable between groups 1 and 2 (G1: median of 1.95 with percentiles of 1.68-2.19 and G2: 1.69 ± 0.44, p=0.0251). The variables epicardial St/SR and global St showed agreement between the two AP4C and LD4C views (95% limits of agreement: -12.81;13.99; -2.405;1.989 and -12.32;10.0 respectively), as well as EF (limit of agreement of 95%: -7.165;6.298 p = 0.2420). In this study, the longitudinal St/SR variables did not detect early systolic dysfunction in the diseased animals and the LD4C view proved to be feasible for obtaining the epicardial St/SR and global St variables, but their values should not be used interchangeably. This view was also feasible to obtain the volumetric variable EF, being useful to assist in the assessment of systolic function in cats. This work is divided into two parts. The first contains a theoretical reference, approaching the main echocardiographic variables (conventional and the 2D-STE tool) used to assess left ventricular systolic function. The second part consists of an article, object of this research, which will later be submitted for publication in the journal Journal of Feline Medicine and Surgery.